EEG signals analysis for motor imagery brain computer interface - Rahman, La z Maruf; Alam, Zawad; Rahman, Md. Musta-E-Nur (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.